Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1994
DOI: 10.1093/clinids/18.5.719
|View full text |Cite
|
Sign up to set email alerts
|

Experience of an Intravenous Therapy Team at the Instituto Nacional de Cancerologia (Mexico) with a Long-Lasting, Low-Cost Silastic Venous Catheter

Abstract: Means of vascular access are fundamental in the management of cancer. However, since current intravenous devices for long-term treatment are expensive and necessitate a high degree of education among medical personnel, in developing countries they are impractical for use in most of the population. We describe the use of a nontunneled, low-cost, long-lasting Silastic catheter (LLSC), cared for by an intravenous therapy team (IVTT), in 462 patients with cancer. The rate of infectious complications was 0.66 infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0
2

Year Published

1998
1998
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 0 publications
1
5
0
2
Order By: Relevance
“…Therefore, high rates of C. parapsilosis recovery could indicate careless CVC handling in many settings [10], [15], [20], [21]. The low prevalence of C. parapsilosis among the populations included in this study confirms the strict policy of CVC care, as seen in previous reports from both participant institutions [22], [23].…”
Section: Discussionsupporting
confidence: 81%
“…Therefore, high rates of C. parapsilosis recovery could indicate careless CVC handling in many settings [10], [15], [20], [21]. The low prevalence of C. parapsilosis among the populations included in this study confirms the strict policy of CVC care, as seen in previous reports from both participant institutions [22], [23].…”
Section: Discussionsupporting
confidence: 81%
“…As it is obviously seen, there are significant differences in the epidemilogical profiles among the areas in our country. Recent studies from other developing countries also report different results [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies from our country reported that the mortality rate among febrile neutropenic patients was 11.6% [16,21].…”
Section: Discussionmentioning
confidence: 99%
“…Una intervención que ha resultado eficaz en este sentido ha sido la creación de equipos de terapia intravenosa notificados por Volkow. 20 Posiblemente otra intervención para reducir la frecuencia de bacteriemias es la creación de centros de mezclas en hospitales, lo cual garantizaría que toda la terapia intravenosa se preparara bajo estrictas condiciones de esterilidad. Por otro lado, el uso de asistencia ventilatoria como factor de riesgo para neumonía nosocomial obliga a garantizar la esterilidad del equipo de inhaloterapia, las bolsas de ventilación y la correcta aspiración de secreciones en pacientes con intubación endotraqueal, de tal manera que se eviten estas complicaciones infecciosas.…”
Section: Discussionunclassified